Obstructed labor and its effect on adverse maternal and fetal outcomes in Ethiopia: A systematic review and meta-analysis - Yordanos Gizachew Yeshitila; Beniam Daniel; Melaku Desta; Getachew Mullu Kassa (PLoS ONE, 2022)
Background Obstructed labor is one of the five major causes of maternal mortality and morbidity in developing countries. In Ethiopia, it accounts for 19.1% of maternal death. The current review aimed to assess maternal and perinatal outcomes of obstructed labor in Ethiopia. Methods Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was followed for this systematic review and meta-analysis. A literature search was made using PubMed/MEDLINE, CINAHL, Summon country-specific search, and Cochrane Libraries’ online databases. Search terms were adverse outcome, obstructed labor, maternal outcome, fetal outcome, and Ethiopia. The Newcastle-Ottawa scale (NOS), based on a star scoring system, was used to assess the quality of the included studies. The meta-analysis was conducted using STATA 16 software. The pooled prevalence of an adverse maternal outcome, fetal outcome, and association between adverse outcome and obstructed labor was calculated using a random-effects model. Egger’s test and funnel plot were used to evaluate publication bias. Result Eighty-seven studies were included in this review, with an overall sample size of 104259 women and 4952 newborns. The pooled incidence of maternal death was estimated to be 14.4% [14.14 (6.91–21.37). The pooled prevalence of uterine rupture and maternal near-miss was 41.18% (95% CI: 19.83, 62.54) and 30.5% [30.5 (11.40, 49.59) respectively. Other complications such as postpartum hemorrhage, sepsis, obstetric fistula, hysterectomy, bladder injury, cesarean section, and labor abnormalities were also reported. The pooled prevalence of perinatal death was 26.4% (26.4 (95% CI 15.18, 37.7). In addition, the association of obstructed labor with stillbirth, perinatal asphyxia, and meconium-stained amniotic fluid was also demonstrated. Conclusions In Ethiopia, the incidence of perinatal and maternal mortality among pregnant women with obstructed labor was high. The rate of maternal death and maternal near miss reported in this review was higher than incidences reported from high-income and most low and middle-income countries. Uterine rupture, postpartum hemorrhage, sepsis, fistula, hysterectomy, and bladder injury were also commonly reported. To improve the health outcomes of obstructed labor, it is recommended to address the three delay models: enhancing communities’ health-seeking behavior, enhancing transportation for an obstetric emergency with different stakeholders, and strengthening the capacity of health facilities to handle obstetric emergencies.